Brentuximab vedotin in CD30+ cutaneous lymphoma: How do we treat, how shall we treat? A review of the literature. (1st December 2017) - Stranzenbach, R.; Dippel, E.; Schlaak, M.; Stadler, R.
Summary: Brentuximab vedotin is an antibody–drug conjugate that brings the antimicrotubule agent monomethyl auristatin E into CD30‐expressing cells. Some prior studies demonstrated good efficacy in cutaneous lymphomas. The standard therapeutic scheme is 1·8 mg kg −1 every 3 weeks. The background of this work is the fact that cutaneous lymphoma has a different pathophysiology and a dynamic other than systemic lymphomas. The objectives of this review were to get an overview of the currently used therapeutic regimen, and to check whether dose reduction or modified time intervals could be of benefit in a similar way with less toxicity. Therefore, we conducted a systematic review of the literature indexed in PubMed and the Cochrane Central Register of Controlled Trials up to April 2016. The procedure was based on the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) criteria. The review showed that the currently used therapeutic regimen is 1·8 mg kg −1 every 3 weeks. No publications of dose‐finding studies in CD30 + cutaneous T‐cell lymphoma (CTCL) were found. Two cases of patients, treated with a dose < 1·8 mg kg −1, have been published. Brentuximab vedotin seems to be a powerful treatment option in refractory CD30 + CTCL, and there is a trend that dose reductions, as well as prolonged treatment intervals, work without any loss of response and with fewer side‐effects.